Integration of halal products with Islamic banking and finance for small and medium enterprise in halal industry - Ishak, Fahrul Irfan (2020)
The increasing population of Muslims around the world has brought a huge impact on all aspects of life. Halal and Islamic banking and finance are two fast growing industries locally and globally. Both industries that based on Shariah jurisdictions contribute crucial significance to the national economy, especially Small and Medium Enterprises (SMEs). The purpose of this study is to examine the opportunities, strengths and challenges of the integration of halal products with Islamic banking and finance in Malaysia. This study is dedicated to Small and Medium Enterprises (SMEs). The significant aspect of this study is the understanding and knowledge of the concept halal and Islamic finance among managers and owners of SME. This study also examines the concept of halal and Thoyyib according to al-Quran and al-Hadith in understanding the integration of halal products with Islamic banking and finance. Qualitative methodology by using document content analysis and interviews is applied in this study. The results of this study found that the meaning of halal not only cover halal product and Islamic finance, but it brought a broader concept including quality, cleanliness, healthy, nutritious and unadulterated. The study also found that the concept of halal and Thoyyib among SME managers only limited to the product and process itself and does not emphasize Shariah compliance in financial matters and causing them not to utilize Islamic banking and finance in their operations. The study also found that halal certification laws and standards do not state the condition of using Islamic banking and finance. However, the practice of halal SMEs that utilizing Islamic banking and finance is a good halal practice and it can be used as a basis towards a more holistic implementation of halal concept. This study found that the challenges that exist are not only related to the law and standard of halal, but also the lack of exposure and knowledge of Islamic banking and financial services among halal SMEs. This study suggests that Islamic banking institutions to enhance Islamic financial assistance schemes for halal SMEs. Various opportunities and incentives need to be provided to halal SMEs to develop the concept of halal integration, namely Halal and Thoyyib as well as Shariah compliance with Islamic and finance system. This study found that the interview with nine (9) halal SME companies are crucial especially their views on halal integration. The interview analysis software used in this study is Atlas t.i 7.0. The study found that the understanding of the concept of halal integration, Islamic banking and finance among halal SMEs is good and there are many opportunities as a strength to realize halal integration concept and strategy. There are many promotion initiatives by the authorities to comprehend national halal agenda such as Halal Parks, conferences, forums, seminars, foreign halal certification bodies and conventions at the national and international level. Finally, in order to comprehend the integration of halal products with Islamic banking and finance among SMEs, the authorities and all parties involved need to be mobilized and strengthened. This should be justified since Malaysia is the world’s leading halal hub.